Diverse sources of resistance to leaf rust in durum wheat - Mishra, A.N.; Kaushal, K.; Dubey, V.G.; Prasad, S.V. Sai (The Indian Journal of Genetics and Plant Breeding, 2016)
Inheritance and extent of diversity for leaf rust resistance were seedling studied among five durum genotypes using pathotype 12-2 (1R5). The F2 and F3 analyses showed that resistance was controlled by one dominant gene each in B 276 and Guji S and by two dominant genes each in AKDW 4339, CPAN 6118 and VD 2001-14. Allelic tests revealed that these genes were different from each other, except the one common between VD 2001-14 and Guji S. Thus, seven diverse genes for leaf rust resistance were identified among the genotypes studied. The identity of these genes is not known. However, they should be different from Lr23 which is common in Indian durum germplasm; and from Lr3, Lr14a, and Lr27+Lr31 among the Lr genes reported in durum wheat, since the pathotype 12-2 (1R5) is virulent to all these genes. The above genotypes can enrich diversity for leaf rust resistance in durum improvement